2018
DOI: 10.1038/s41375-018-0188-8
|View full text |Cite
|
Sign up to set email alerts
|

Time resolved quantitative phospho-tyrosine analysis reveals Bruton’s Tyrosine kinase mediated signaling downstream of the mutated granulocyte-colony stimulating factor receptors

Abstract: Granulocyte-colony stimulating factor receptor (G-CSFR) controls myeloid progenitor proliferation and differentiation to neutrophils. Mutations in CSF3R (encoding G-CSFR) have been reported in patients with chronic neutrophilic leukemia (CNL) and acute myeloid leukemia (AML); however, despite years of research, the malignant downstream signaling of the mutated G-CSFRs is not well understood. Here, we used a quantitative phospho-tyrosine analysis to generate a comprehensive signaling map of G-CSF induced tyrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 32 publications
1
51
0
Order By: Relevance
“…The truncation mutations, which also occur in SCN, largely coexisted with membrane proximal or transmembrane CSF3R mutations as compound mutations . Mechanistically, the membrane proximal mutations prevent O ‐glycosylation of CSF3R resulting in increased active dimeric configuration, ligand‐independent receptor activation, and constitutive downstream signaling through JAK2 (and potentially Brutonʼs tyrosine kinase according to a recent report). On the other hand, receptor truncation involves a loss of negative regulatory motifs including the dileucine sorting motif, which plays a role in receptor internalization, and binding sites for the suppressor of cytokine signaling 3 (SOCS3) which targets the receptor for degradation .…”
Section: Molecular Pathogenesismentioning
confidence: 99%
“…The truncation mutations, which also occur in SCN, largely coexisted with membrane proximal or transmembrane CSF3R mutations as compound mutations . Mechanistically, the membrane proximal mutations prevent O ‐glycosylation of CSF3R resulting in increased active dimeric configuration, ligand‐independent receptor activation, and constitutive downstream signaling through JAK2 (and potentially Brutonʼs tyrosine kinase according to a recent report). On the other hand, receptor truncation involves a loss of negative regulatory motifs including the dileucine sorting motif, which plays a role in receptor internalization, and binding sites for the suppressor of cytokine signaling 3 (SOCS3) which targets the receptor for degradation .…”
Section: Molecular Pathogenesismentioning
confidence: 99%
“…[1][2][3][4] Previous studies have reported somatic mutations in CSF3R cytoplasmic domain (most frequent Q741x) in the SCN patient cohorts undergoing prolong G-CSF therapy. [5] In our previous studies, [6,7] we have presented phosphoproteomics datasets pointing to aberrant signaling through Bruton's tyrosine kinase (BTK) [6] and many of other phospho-Ser/Thr signaling changes between the normal and mutated G-CSFRs. [7] Aberrant activation of BTK was validated in mouse as well as human models.…”
Section: Doi: 101002/prca201900144mentioning
confidence: 99%
“…[7] Aberrant activation of BTK was validated in mouse as well as human models. [6] Furthermore, a significant reduction in the overall leukemic potential of the mutated G-CSFRs expressing primary cells were reported after ibrutinib (FDA approved BTK inhibitor) treatment. [6] However, the signaling mechanism of ibrutinib's action is not fully known.…”
Section: Doi: 101002/prca201900144mentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of total 137 DEGs was shown in heatmap, which was shown the relative expression level of DEGs( Fig. 2A) [19][20]. Then the 137 DEGs were verified by the DEGs PPI network tool of STRING, which included 243 edges and 104 nodes.…”
Section: Ppi Network and Core Genes Analysismentioning
confidence: 99%